PATTERN OF SUICIDE DEATHS: A RETROSPECTIVE 5-YEAR AUTOPSY SAMPLE ANALYSIS IN PAKISTAN - Imran, Nazish; Tariq, Fareeha; Bhatti, Izwa; Tariq, Summaiya Syed; Ali, Riasat; EhsanUllah, Hafsah (Journal of Pakistan Psychiatric Society, 2022)
Objective: Suicide is a global public and mental health problem. In this study, we evaluated autopsy reports of suicidal deaths for 5 years to study the demographic distribution of the suicide victims, and methods of suicides.Methods:It is a descriptive cross-sectional study of suicide autopsies conducted at the mortuaries of two large Forensic departments in Punjab and Sindh (King Edward Medical University/Mayo hospital, Lahore, and Jinnah Postgraduate Medical Centre Karachi) for 5 years, between January 2017-December 2021. Data was collected on pre-designed proformas and was statistically analysed using SPSS 26.Results:Between 2017 and 2021, 98 cases of suicide were examined in the two study centres (67 males ,68.4% and 31 females, 31.6 %). Fifty-six suicides (57%) were in age group under 30 years old. The most frequently used methods for suicide were hanging (41,41.8%) , use of firearms (23, 23.5%), Self-poisoning (11,11.2%), and jumping from heights (6, 6.1%). Significant differences were noted regarding method of suicide among gender and different age groups as well as different study centres (P value<.05). Firearms were used solely by males, and all deaths due to jumping from heights were in Karachi.Conclusion:Due to local cultural and religious beliefs, the autopsy rate in suicide seems too low. There was a male preponderance amongst suicidal death autopsies in our study sample. Hanging  Firearms and self-poisoning were the most frequent suicidal methods. Provision of psychological and social supports along with restriction to easy access to firearms and poisons should be considered by policy making and healthcare authorities to tackle this preventable public health problem.